Developing an Accounting Textbook Using Collaborative Learning and IFRS for Senior High School Students in Indonesia - Irafahmi, Diana Tien; Sulastri, Sulastri (Asian Journal of Accounting Research, 2016)
The 2013 curriculum mandates the importance of collaborative learning designed to educate students to be more productive, creative, and innovative with a high level of affective skills. Collaborative learning can be manifested in the form of a textbook. This research is aimed at developing an accounting textbook in accordance with the mandate of the 2013 curriculum. The selected model is IDI which consists of three main phases: defining, developing and evaluating. The methods chosen are interview, observation, and document review which are analyzed qualitatively. The research was conducted in 4 senior high schools in Malang. The finding shows that at defining phase, there is a need to develop an accounting textbooks using collaborative learning and corresponding to the new accounting standards, namely IFRS. Therefore, at the developmental phase, we construct a prototype book ready to be evaluated. The result of evaluation phase shows that the textbook is valid on the overall aspects including the content, the presentation, the graphic, and the language, with an average percentage of 93.7%.